Characterizing Neurocognitive Impairment in Juvenile Fibromyalgia Syndrome: Subjective and Objective Measures of Dyscognition - Gmuca, Sabrina; Sonagra, Maitry; Xiao, Rui; Mendoza, Elizabeth; Miller, Kimberly S.; Thomas, Nina H.; Young, Jami F.; Weiss, Pamela F.; Sherry, David D.; Gerber, Jeffrey S. (Frontiers in Pediatrics, 2022)
Objectives: Our understanding of brain fog, or dyscognition, among youth with juvenile fibromyalgia syndrome is limited. We aimed to determine the prevalence of subjective (self-reported) and objective dyscognition, as well as factors associated with subjective dyscognition in juvenile fibromyalgia syndrome. Methods: A cross-sectional cohort study of patients 12-17 years old (n=31) diagnosed with primary juvenile fibromyalgia syndrome and one of their parents from 2017-2019. Subjects completed a series of survey measures and patients completed a brief neurocognitive battery. Subjective dyscognition was determined based on scores on the Pediatric Quality of Life Inventory (PedsQL) Cognitive Functioning Scale and Behavior Rating Inventory of Executive Function (BRIEF-2) global executive composite (GEC). Objective dyscognition was defined as impairment of more than two standard deviations in any of the neurocognitive domains. We used Fisher’s exact test or Wilcoxon rank-sum test, as appropriate, to compare clinical patients based on the presence of dyscognition. Multivariable logistic regression modeling was performed to determine factors associated with subjective dyscognition. Results: Of the 31 subjects, 65% reported subjective dyscognition and 39% had objective dyscognition, primarily in the domains of psychomotor speed (23%), executive function (23%), and attention (3%). Subjective dyscognition was not indicative of objective dyscognition. Subjective dyscognition was independently associated with functional disability (OR: 1.19 [95% CI: 1.02-1.40]) and anxiety (OR: 1.12 [95% CI: 1.02-1.24]). Discussion: Adolescents with fibromyalgia predominantly experience subjective dyscognition but more than 1/3 also experience objective dyscognition. Future research should explore the impact of interdisciplinary rehabilitation programs on the treatment of dyscognition in youth with JFMS.